Histopathological spectrum of lesions in gastrointestinal endoscopic biopsies in Jawahar Lal Nehru Medical College and associated group of Hospitals, Ajmer, Rajasthan - Machiwal, Kishan; Menghani, Bhawika; Kasliwal, Neena; Sharma, M. P. (International Journal of Research in Medical Sciences, 2022)
Background: The gastrointestinal tract which extends from the esophagus to anus is a common site for numerous pathological processes from non-neoplastic, pre-neoplastic, to neoplastic. Gastrointestinal tumors including both benign and malignant tumors are the major cause of morbidity and mortality worldwide. Endoscopy in combination with endoscopic biopsy plays an important role in detecting early cancers and/or high-grade dysplasia and in the diagnosis of upper and lower gastrointestinal tract neoplasms and therefore aids in their early management. Methods: This study was done for 1 year from July 2018 to June 2019 (retrospectively) and over a period of 1 year from July 2019 to June 2020 (prospectively). All endoscopic biopsies samples were received in the department of pathology at J. L. N. Medical College and Associated Group of Hospital, Ajmer, Rajasthan. Results: The mean age of patients were 51.91±18.86 years and highest incidence of gastrointestinal (GI) disease was seen between the age group of 51-60 years. The male: female (M: F) ratio was 1.46: 1. Non neoplastic lesions are more common than neoplastic lesions. Inflammatory lesion was the most commonly observed lesion followed by malignant lesions. The sensitivity of endoscopy is 96.25%, specificity is 68.67%, the positive predictive value is 74.76% and the negative predictive value is 95%. Accuracy for diagnosis by endoscopy is 82.21%. Conclusions: Endoscopic biopsy correlation reflects important advances in understanding the pathophysiology of disease and prognosis and survival rates after staging in the case of carcinomas. It provides diagnostic information and aids in improving patient management.